Εosinophilic Chronic Obstructive Pulmonary Disease. What Do We Know So Far? - Konstantinos Bartziokas; Andriana I. Papaioannou; Nikoletta Rovina; Georgia Papaiakovou; Stelios Loukides; Paschalis Steiropoulos (Pulmonary Therapy)
Abstract The latest advances in asthma treatment have highlighted the significance of eosinophilia and the possible role of some pro-eosinophilic mediators, like interleukins (IL) IL-5, IL-4/IL-13, and IL-33 in the disease’s pathogenesis. Considering that a subgroup of patients with chronic obstructive pulmonary disease (COPD) may have blood eosinophilia akin to that seen in asthma, numerous studies in the last decade have suggested that eosinophilic COPD is a separate entity. While the exact role of blood eosinophils in the pathophysiology of COPD remains unclear, eosinophilia seems to increase the effectiveness of corticosteroid therapy. Currently, monoclonal antibodies targeting the interleukins (IL-5, IL-4, IL-13, and IL-33) or their receptors are being investigated in patients with COPD belonging in T2-high endotype. This review focuses on the mechanisms of eosinophilia in COPD, the effects of eosinophilia on disease outcome, and examines the most recent data on the use of peripheral blood eosinophilia in treating patients with COPD. Finally, we emphasize the current implication of monoclonal antibodies in COPD in the context of eosinophilic airway inflammation.